Physical Activity, Physical Performance, and Biological Markers of Health among Sedentary Older Latinos. (16th June 2014) - Moreno, Gerardo; Mangione, Carol M.; Wang, Pin-Chieh; Trejo, Laura; Butch, Anthony; Tseng, Chi-Hong; Sarkisian, Catherine A.
Abstract : Background . Physical activity is associated with better physical health, possibly by changing biological markers of health such as waist circumference and inflammation, but these relationships are unclear and even less understood among older Latinos—a group with high rates of sedentary lifestyle. Methods . Participants were 120 sedentary older Latino adults from senior centers. Community-partnered research methods were used to recruit participants. Inflammatory (C-reactive protein) and metabolic markers of health (waist circumference, HDL-cholesterol, triglycerides, insulin, and glucose), physical activity (Yale physical activity survey), and physical performance (short physical performance NIA battery) were measured at baseline and 6-month followup. Results . Eighty percent of the sample was female. In final adjusted cross-sectional models, better physical activity indices were associated with faster gait speed (P < 0.05 ). In adjusted longitudinal analyses, change in self-reported physical activity level correlated inversely with change in CRP (β = - 0.05 ; P = 0.03 ) and change in waist circumference (β = - 0.16 ; P = 0.02 ). Biological markers of health did not mediate the relationship between physical activity and physical performance. Conclusion . In this community-partnered study, higher physical activity was associated with better physical performance in cross-sectional analyses. In longitudinal analysis, increased physical activity was associated with improvements in some metabolic and inflammatory markers of health.